Analisa proses pirolysis dengan variasi jumlah tabung pembakaran terhadap Karaktristik hasil bio-oil - Kemas Ridhuan; Edi Winarno; Dwi Irawan (TURBO [Tulisan Riset Berbasis Online], 2022)
Bio-oil is a blackish liquid fuel derived from biomass such as corn cobs, rice husks and other biomass such as cocoa shells. The organic acid content in bio-oil gives bio-oil acidic properties. Bio-oil can be obtained in the pyrolysis combustion process, using a combustion tube. The number of tubes used can affect the yield characteristics of bio-oil. The purpose of this study was to determine the characteristics of bio-oil bio-oil produced by varying the number of combustion tubes in the pyrolysis process. Such as pyrolysis time, amount of bio-oil, temperature and content of bio-oil. This research method utilizes cocoa shell biomass waste to turn into bio-oil with a pyrolysis process, namely by varying the number of combustion tubes, namely one tube, two tubes and three tubes with a diameter of one tube 27.74 cm, two tubes 19.6 cm and three tubes 16 cm with the same cylinder volume of 18.7 cm3, by carrying out the prolysis process, namely putting the cocoa shell waste into the combustion tube and closing it. Then the combustion tube is inserted into the pyrolysis reactor and then closed and then burned. From the results of the research, the results of bio-oil in a single tube of raw material were 130 ml with a processing time of 113 minutes and bio-oil characteristics, a calorific value of 2177,464 cal/g, a viscosity of 1,574 CPs, and a pH of 4.77. Whereas in the second raw material tube, there were 80 ml with a processing time of 105 minutes and specifications for bio-oil, a calorific value of 2071,151 cal/g, a viscosity of 1,780 CPs and a pH of 4.96. While the three raw material tubes were 50 ml with a processing time of 100 minutes, and bio-oil specifications, calorific value 1983,950 cal/g, viscosity 2,626 CPs and pH 5.42.